2022
DOI: 10.30541/v47i4iipp.763-778
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Fiscal Theory of Price Level in Case of Pakistan

Abstract: There are two competing views of the interaction between monetary and fiscal policy and their effects on price stability for policy-maker’s point of view. In the classical view, in Ricardian regimes it is the demand for liquidity and its evolution over time that determines prices. In such a regime fiscal policy is passive, which implies that government bonds are not net wealth [Barro (1974)], and monetary policy works through the interest rate or another instrument to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…There are, however, two competing views on the interaction between monetary and fiscal policies and their effects on price stability. The classical view of Ricardians argues that it is the demand for liquidity and its progress over time that defines the path of prices (Attiya et al, 2008). In such rule, fiscal policy is passive, suggesting that government bonds are not net wealth, and monetary policy works through interest rates to determine prices.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, two competing views on the interaction between monetary and fiscal policies and their effects on price stability. The classical view of Ricardians argues that it is the demand for liquidity and its progress over time that defines the path of prices (Attiya et al, 2008). In such rule, fiscal policy is passive, suggesting that government bonds are not net wealth, and monetary policy works through interest rates to determine prices.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
“…In such rule, fiscal policy is passive, suggesting that government bonds are not net wealth, and monetary policy works through interest rates to determine prices. The Ricardian view assumes that price levels are mainly determined by money supply in the long run (Attiya et al, 2008). The Ricardian equivalence, according to Barro (1974Barro ( , 1989, is based on a monetarist view on inflation that government deficit or public debt does not have a significant impact in the determination of price level, implying that government bonds are not net wealth.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
“…A feedback from the level of debt ratio to taxes and government spending is necessary for stability of the debt, unless the rate of growth of the economy is exactly equal to the average cost of financing the debt. Such a feedback is a feature of the Pakistani fiscal data as is revealed by a positive correlation between the government surplus-to-GDP ratio and the government debt-to-GDP ratio [Javid, Arif, and Sattar (2008)]. The interest rates, an important variable in the transmission of fiscal shocks, depend on future expected monetary policy and on the risk premium: both may be affected by the debt dynamics.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Instead, their findings suggested that a non-Ricardian or FD regime was present in Turkey, mainly after the 1980s due to the increasing cost of debt and the financial liberalization. Javid, Arif, and Sattar (2008) implemented a VAR approach based on Canzoneri et al to analyse the FTPL assumptions in Pakistan for the period 1971-2007. They found mixed results: 1) liabilities decrease as a response to higher surplus; this is in line with a Ricardian (MD regime); 2) as predicted by the FTPL, the wealth effect of changes in nominal public debt seems to increase prices and therefore to drive inflation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar non-Ricardian evidence was reported by Tanner and Ramos (2003) for Brazil and Bildirici and Ersin (2005) for Turkey. However, evaluating only the full sample might lead to misleading conclusions, as Javid, Arif, and Sattar (2008) suggested.…”
Section: Svar Approachmentioning
confidence: 99%